International Academic Mobility as a Capacity Building Factor in Higher Education - Dabney-Fekete, Ilona Dóra (Central European Journal of Educational Research, 2020)
International academic mobility means the teaching or research activity of higher educational instructors or researchers, which spans a couple of days or a few months, during which individual professional growth, the establishment of international cooperation and networks, personal relations and friendships may develop. It is also considered to be a fundamental necessity for building capacity and an outstanding supremacy, even if a country’s academic resources are modest. Thus it is crucial to gain information about its current and actual state, quality, standards, struggles and the direction it is heading towards. As a part of a bigger research study, we wanted to know how international academic mobility, used for capacity building, changes over time, and whether country-specific features and patterns could be traced. In this present study we made an attempt to uncover the international activity based on the academic mobility of the full-time instructors at two Hungarian higher educational institutions. One of them is a large university that plays a leading role in internationalization. The other is a dynamically developing regional knowledge center. We examined the instructors of two faculties from the first, and everybody from the regional knowledge center, since it is smaller in size. Altogether 210 instructors responded to our 60 questions in the survey. The surveys were processed in the SPSS statistical analysis program. Concerning the examined discussions, categories and proposed topics, our research was built upon two previously carried out investigations – a Hungarian and a Norwegian one. We found that in Hungary in the given time period (2012-2014), the instructors with the strongest international activity were: 1. the men; 2. those who held higher academic positions; 3. those who were married or were in a relationship; and 4. who were from the field of social science.